Large urban development projects in company towns. The cases of Erlangen (Siemens) and Basel (Novartis) - Bertram, Dominik; Chilla, Tobias; Pfister, Marc (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
The literature on large-scale urban development projects often primarily addresses drastic failures and their underlying causes. Recently, however, success factors have also received increasing attention. From both perspectives, management approaches, participation logics and political strategies are prominent topics in this context. However, the symbolic dimension of large urban development projects is rarely considered. This is somewhat surprising, as symbolic meaning is considered key to urban development in many contexts. We explore this dimension with two cases of urban entrepreneurial development projects, the Novartis Campus in Basel (Switzerland) and the Siemens Campus in Erlangen (Germany). Our empirical study relies on thematic press analyses. We reflect on the postulate that a “fit” between urban symbolism and societal expectations is a crucial determinant of smooth implementation in large-scale urban development projects in company towns. In both case studies, urban integration, architecture and design are of great relevance. These “soft” factors in planning and implementation suggest that the outcomes are not solely dependent on technical professionalism. Instead, the appropriate symbolism within the urban context and the associated project investment emerge as critical factors.